Distinct circular RNA expression profiles in pediatric ependymomas. (29th January 2021) - Ahmadov, Ulvi; Bendikas, Meile M.; Ebbesen, Karoline K.; Sehested, Astrid M.; Kjems, Jørgen; Broholm, Helle; Kristensen, Lasse S.
Abstract: Pediatric ependymomas frequently develop in the cerebellum and are currently treated using non‐specific therapies, in part, because few somatically mutated driver genes are present, and the underlying pathobiology is poorly described. Circular RNAs (circRNAs) constitute as a large class of primarily non‐coding RNAs with important roles in tumorigenesis, but they have not been described in pediatric ependymomas. To advance our molecular understanding of ependymomas, we performed Next Generation Sequencing of rRNA‐depleted total RNA of 10 primary ependymoma and three control samples. CircRNA expression patterns were correlated to disease stage, outcome, age, and gender. We found a profound global downregulation of circRNAs in ependymoma relative to control samples. Many differentially expressed circRNAs were discovered and circSMARCA5 and circ‐FBXW7, which are described as tumor suppressors in glioma and glioblastomas in adults, were among the most downregulated. Moreover, patients with a dismal outcome clustered separately from patients with a good prognosis in unsupervised hierarchical cluster analyses. Next, NanoString nCounter experiments were performed, using a custom‐designed panel targeting 66 selected circRNAs, on a larger cohort that also included medulloblastomas and pilocytic astrocytomas. These experiments indicated that circRNA expression profiles are different among distinct pediatric brain tumor subtypes. In particular, circRNAs derived from RMST, LRBA, WDR78, DRC1 and BBS9 genes were specifically upregulated in ependymomas. In conclusion, circRNAs have different expression profiles in ependymomas relative to controls and between survivors and patients with a dismal outcome, suggesting that circRNAs could be exerted as diagnostic and prognostic biomarkers in the future if further validated in larger cohorts.